Institutions and managerial task allocation: evidence from Chinese entrepreneurs - Guo, Di; Jiang, Kun; Xu, Chenggang (University of Chicago Press, 2017)
This study presents theoretical and empirical analyses of the time allocation of entrepreneurs as a response to weak property rights protection. Using a nationwide random-sample survey of more than 3,000 entrepreneurs in over 100 cities in China, we find that entrepreneurs, responding to the violation of property rights, spend large proportions of their working time on lobbying activities to protect their businesses at a cost to management time. Moreover, the sensitivity of lobbying time to property rights protection is reduced if the entrepreneur is politically connected or if the firm is larger or older.